Clinical overview of anti-CD19 BiTE® and ex vivo data from anti-CD33 BiTE® as examples for retargeting T cells in hematologic malignancies. Issue 2 (October 2015) - Zugmaier, Gerhard; Klinger, Matthias; Schmidt, Margit; Subklewe, Marion
Highlights: Bispecific T-cell engager (BiTE ® ) molecules are single-chain antibody constructs that lead to target-dependent activation and proliferation of T cells. BiTE ® molecules redirect T cells to target cells, causing target-specific serial cell lysis. Blinatumomab has shown anticancer activity in clinical trials in leukemia/lymphoma. In primary samples from patients, AMG 330 has shown promising antileukemia activity. Abstract: Blinatumomab, a bispecific antibody construct targeting CD19, is the most advanced member of bispecific T-cell engager (BiTE ® ) molecules. The clinical development program includes B-precursor acute lymphoblastic leukemia (ALL) and B-cell non-Hodgkin lymphoma (NHL). Minimal residual disease (MRD) response in patients with MRD-positive B-precursor ALL has translated into long-term clinical benefits as demonstrated by an estimated relapse-free survival (RFS) of 60% with sustained MRD negativity at a follow-up of 31 months. Remissions induced in pediatric and adult patients with relapsed/refractory B-precursor ALL have allowed for successful allogeneic hematopoietic stem cell transplantation (HSCT) in this setting. Blinatumomab has also induced durable responses in low-grade B-cell NHL. Blinatumomab recently gained approval in the United States by the U.S. Food and Drug Administration for treatment of Philadelphia chromosome-negative B-precursor relapsed/refractory acute lymphoblastic leukemia. AMG 330 is an investigational anti-CD33 BiTE ® antibody construct. Targeting CD33 ex vivo in primary samples from patients with acute myeloid leukemia (AML) has shown AMG 330-mediated T-cell expansion and T-cell cytotoxicity against AML cells.